Proposta de ferramentas interpretativas do patrimônio para o atendimento das visitas no Jardim Botânico de Santa Maria – RS - Silva, Daniele Reginato da (2024)
In the context of contemporary society, there is an increase in interest in environmental tourism, and contact with nature through moments of leisure and travel and experiences that enable knowledge of natural diversity in a sustainable way. From the Brazilian Network of Botanical Gardens, the existence, in the state of Rio Grande do Sul (RS), of four botanical gardens is verified, located in the municipalities of Porto Alegre, Caxias do Sul, Lajeado and Santa Maria. The National Council for the Environment (CONAMA), in Brazil, defines that botanical gardens as protected areas that house collections of living plants that are “scientifically recognized, organized, documented and identified, for the purpose of study, research and documentation of the floristic heritage of the region”. Country, accessible to the public, in whole or in part, serving education, culture, leisure and environmental conservation” (CONAMA, 2003). People's search for enjoying natural areas has gradually increased, but the municipality of Santa Maria has a limited supply of green spaces for socializing, whether public or private. The botanical garden has the ability to give new meaning to urban space, both from the point of view of leisure for residents and tourism potential. Therefore, this study aimed to create a proposal for an interpretative and tourist guide with the selection of twenty-five specimens of native plants predominant in Rio Grande do Sul, which are part of the collection of the Botanical Garden of the Federal University of Santa Maria (UFSM). The methodology adopted was qualitative, with bibliographical review; non-participant observation and on-site visits under guidance, to identify and select the species that make up the proposed final product of the dissertation. As a result, a tourist guide and a sticker card were created that enable the interpretation of natural heritage, and are a means of promoting tourist promotion of the garden, encouraging local people and visitors to visit the botanical garden spaces on site. It is expected to make the material available as a resource from the perspective of environmental/tourist outreach actions developed with the target audience of the university's Botanical Garden. This research was developed in the Graduate Program in Cultural Heritage at the Federal University of Santa Maria, in the area of concentration Architecture and Material Heritage within the research line Preservation of Material Heritage.